2014
DOI: 10.1024/0300-9831/a000213
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake, Changes in Lipid Parameters and the Risk of Hypertriglyceridemia: A Prospective Approach in the Tehran Lipid and Glucose Study

Abstract: These findings suggested that more dense diets, and a higher intake of fast food and fat, could have undesirable effects on lipid and lipoprotein levels; in contrast, higher intakes of fiber, and phytochemical rich foods, especially whole grain and legumes, could have protective effects against undesirable changes in lipid and lipid profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In contrast, in a longitudinal study among Iranian adults DED was inversely associated with HDL-C and positively related to atherogenic index of plasma changes. 45 In another epidemiologic research in Iran, findings showed that higher intake of ED foods lead to higher serum HDL and TG in female nurses. 12 The discrepancies among studies may be partly related to specific characteristics of diet in each population because DED do not differentiate foods in terms of energy.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, in a longitudinal study among Iranian adults DED was inversely associated with HDL-C and positively related to atherogenic index of plasma changes. 45 In another epidemiologic research in Iran, findings showed that higher intake of ED foods lead to higher serum HDL and TG in female nurses. 12 The discrepancies among studies may be partly related to specific characteristics of diet in each population because DED do not differentiate foods in terms of energy.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, intake of fresh fruits, fresh vegetables, and whole grains would reduce the dietary Na/K ratio and improve serum TG levels. The results of Mirmiran et al support this speculation: fast food intake was positively associated with serum TG, and a higher dietary Na/K ratio increased the risk of hTG by 63% [ 46 ]. Our findings detecting an association between dietary Na/K ratio and hTG further highlight the importance of reducing Na and increasing K intake and provide a guide for potential interventional targets to decrease the risk of hTG.…”
Section: Discussionmentioning
confidence: 95%
“…Participants in the highest compared to the lowest quartile of dietary fiber and phytochemical-rich foods decreased risk of incident hypertriglyceridemia by 42% after 3 years of follow-up. In addition, higher dietary sodium to potassium ratios compared to lower ratios increased the risk of hypertriglyceridemia by 63% (77). Med score was not associated with components of MetS (23).…”
Section: Methodsmentioning
confidence: 99%